Perancangan Tampilan Antarmuka Pengguna Aplikasi Web Praktik Kerja Industri (Prakerin) menggunakan Metode Design Thinking. (Studi Kasus: SMKN 2 Singosari) - Maya Dwi Wijayanti; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Industrial Work Practice (Prakerin) is a mandatory activity held by every vocational high school (SMK) which is carried out for up to one year. During carrying out these activities, students are required to perform all sequences of activities manually or offline. Activities carried out manually are considered difficult from the side of students and teachers who have to manually ask the company, especially in this digital era. The existence of this internship web application will later be able to support and simplify the entire process of these activities, starting from information on companies that have collaborated, registration of activities, licensing activities, monitoring the activity process, to assessment and reporting. Before making the website application, of course, it is necessary to design a user interface. So a user interface design was made on the Industrial Work Practice (Prakerin) web application at SMKN 2 Singosari. In this study, the researcher decided to use the Design Thinking method in implementing the design implementation. This method has stages, namely Empathize which is a data collection process, Define is a problem analysis process and needs exploration, Ideate is the process of getting ideas and solutions, Prototype which is the process of implementing ideas and solutions into user interface designs and Testing, namely design testing. interface to the user. After being tested, the results of the design get a test score of 83, which can be categorized into a proper design as a school website application.